2005
DOI: 10.5688/aj690109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative NAPLEX Performance of Graduates of US Pharmacy Programs Accredited by ACPE Prior to and Since 1992

Abstract: Objective. To assess the performance on the standardized licensure examination for graduates from "newly accredited" versus "more established" pharmacy programs. Methods. The performance of graduates from newly accredited programs (those receiving initial full accreditation since 1992) was compared with graduates of more established programs (those receiving initial full accreditation prior to 1992). North American Pharmacy Licensing Examination (NAPLEX) data for first-time test takers during the May-August wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The details of the included studies and their findings are summarized in Table 1. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Of the excluded articles, 3 were duplicate information (ie, a poster which was later published as full-text), 8 articles were commentaries, editorials, or non-peer reviewed publications, 5 articles did not have NAPLEX passing as an outcome, 3 articles correlated NAPLEX passing after a change in the curriculum, and 1 article reported correlation between the student characteristics with pre-NAPLEX scores. The included studies were published over a period of 15 years from 2005 to 2020, investigated NAPLEX passing from pharmacy programs ranging from a single institution to 137 institutions, and collectively covered over 13,000 individual students' NAPLEX results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the included studies and their findings are summarized in Table 1. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Of the excluded articles, 3 were duplicate information (ie, a poster which was later published as full-text), 8 articles were commentaries, editorials, or non-peer reviewed publications, 5 articles did not have NAPLEX passing as an outcome, 3 articles correlated NAPLEX passing after a change in the curriculum, and 1 article reported correlation between the student characteristics with pre-NAPLEX scores. The included studies were published over a period of 15 years from 2005 to 2020, investigated NAPLEX passing from pharmacy programs ranging from a single institution to 137 institutions, and collectively covered over 13,000 individual students' NAPLEX results.…”
Section: Resultsmentioning
confidence: 99%
“…The three nation-wide, multiinstitution studies evaluated only the characteristics of the programs and not the student variables. 9,26,27 To comprehensively determine the predictability of student-dependent characteristics for NAPLEX success, a large-scale study of all pharmacy programs would be warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The NABP used a 3-parameter Item Response Theory model to calculate test takers' scaled score (ranges from 0 to 150, with 75 as a cutoff for a passing scaled score). 26 A few teams faced challenges in their electronic communications, as would be expected with a distance project. Many teams reported that 100% of their work was done electronically because of their varied geographic locations.…”
Section: 53mentioning
confidence: 99%